소비자 비만관리 행동에 있어 자아개념과 주관적 규범의 영향 및 자기통제감의 조절변수적 영향 - 정형식(Hyung Shik Jung); 김영심(Young Shim Kim) (Asia Marketing Journal (Online), 2006)
It is frequently observed that consumers' behavior and performance in their weight control are greatly affected by the degree of self-control by the consumers themselves. In other words, effective weight control behavior is only possible when the consumers invest a substantial amount of endeavors and self-control. The present study empirically investigated the effect of the self-image congruence and subjective norm formed by self- concept reflected in weight control behavior on weight control attitude formation, actual behavior, and performance. For more in-depth research, rather than simply showing differences in performance based on self-control, the present study divided the subjects into high and low self-control groups for a comparative purpose. Based on empirical research employing general consumers and those who were engaged in an actual weight loss program at professional weight control centers as subjects, the study found the following results: First, for both high and low self-control groups, self-image congruence significantly affected attitude toward weight control, but not the actual weight control behavior. The results indicate that in weight control, the actual behavior must be preceded by the attitude. Second, subjective norm directly affected both attitude toward weight control, and behavior for the low self-control group while it affected the behavior only for the high self-control group. The results show that the lower self-control is, the more powerful the effect of referents is. Third, weight control attitude positively affected weight control behavior only for the high self-control group. Fourth, weight control behavior significantly affected the performance for both high and low self-control groups. Compared to the low group, the high self-control group showed more powerful effect of behavior, suggesting the crucial role of self-control in successful weight control. The results also imply that the role of referents is relatively more important for the low self-control group. 소비자의 비만관리 행동 및 성과는 소비자 자신의 통제정도에 따라 크게 차이가 난다는 것이 일반적으로 관찰된다. 실제 비만관리 성과는 소비자 자신이 상당한 정도의 자기 노력과 통제를 투입해야만 달성된다. 본 연구는 자기통제감에 따른 단순한 성과의 차이만을 보기보다는 자기통제감을 고·저집단으로 분류하여 비만관리 행동상의 자아개념을 통한 자아이미지 일치감 및 주관적 규범이 비만관리의 태도형성과 행동 및 성과에 미치는 인과관계 과정을 실증적으로 검증하였다. 일반소비자와 실제 전문적인 비만관리 시설에서 비만관리를 하고 있는 소비자를 대상으로 실증분석한 결과는 첫째, 자기통제감 고·저집단 모두에서 자아이미지 일치감은 비만관리의 태도형성에 유의한 영향을 미치는 것으로 나타났으나 비만관리 행동에는 유의한 영향을 미치지 않는 것으로 나타났다. 이에 소비자의 비만관리 행동은 태도를 형성하지 않고는 직접적으로 행동을 이끌지 못하는 것을 알 수 있다. 둘째, 자기통제감 저집단에서는 주관적 규범이 비만관리의 태도 및 비만관리 행동에 모두 직접적인 영향을 미치는 것으로 나타났으나 자기통제감 고집단은 주관적 규범이 비만관리 행동에만 유의한 영향을 미치는 것으로 나타나, 자기통제감이 낮을수록 가까운 준거인들의 영향력이 크다는 것을 보여주고 있다. 셋째, 자기통제감 고집단만이 비만관리의 태도가 비만관리 행동에 긍정적 영향을 미치는 것으로 나타났다. 넷째, 자기통제감 고·저집단 모두에서 비만관리 행동이 비만관리 성과에 유의한 영향을 미치는 것으로 나타났다. 이들의 상대적 영향력을 비교한 결과, 자기통제감 고집단이 저집단보다 더 큰 영향력을 나타내 소비자의 비만관리 행동의 성과를 높이기 위해서는 자기통제감의 역할이 크다는 것을 알 수 있다. 한편 자기통제감 저집단은 준거인의 역할이 상대적으로 중요하다는 것을 시사하고 있다.